Konstruksi Citra Negara dan Diplomasi Publik melalui @America di Kalangan Masyarakat Muslim Indonesia - Harry; Samiaji, Andis; Bahruddin, Muh.; Hidayat, Endik (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Nation image in the international league possess an urgent task, especially when a country is establishing a relationship and running a strategical errand across the world. United States is one of such country that has their diplomats towards numerous countries and it is important for them to build and maintain their image. This is done in order to maintain the authority order in other countries, such as Indonesia. Despite valuing human rights and freedom, United States of America’s reality is far from the claim. Several cases such as War on Terrorism has received many critics since the 9/11 tragedy. This phenomenon is not only considered a discrimination towards Muslim community across the globe, but also has taken numerous lives in the process. As the result, Indonesia’s perception towards the United States is gradually deteriorating over time, which leads to the US’ policy to build their first cultural center, fueled by state of the art technologies, named @america. This facility has proven to be a positive image for United States towards Indonesians, especially Muslims.